The study of academic self-efficacy of the students studying in the departments of physical education and sport - Y. Sinan Bırıcık; Emre Bellı (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to analyze academic self-efficacy of the students who study at the faculty of sports sciences and Kazım Karabekir Faculty of Education in Atatürk University. In the study, in order to gather data about their self-efficacy, the scale of “academic self-efficacy” which was developed by Owen amp; Froman and was adapted to Turkish language by Ekici, was applied to 161 male and 84 female students, 245 in total, ın the analysis of the obtained data, in the SPSS programme, such tests were applied on frequence analysis, t-test and varience analysis (Anova), for independent groups, and so asto find out where they are originated from, scheffe test was applied. While comparing the sub-dimensions of academic self-efficacy of the attendants according to their engagement in sports regularly, any significant differences were not encountered in the sub-dimensions of cognitive practices (p lt;0.05) and technical skills (p lt;0.05) of the attendants, yet, a significant difference was encountered in the sub-dimensions of social status (p lt;0.05). According to this data, it can be seen that the students who do sports regularly have higher level of academic self-sufficiency in proportion to the students who do not do any sports regularly in the sub-dimension of social status.